(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
The study assessed the carbon and nitrogen stocks in the soil solum of cassava and rice farms in the derived savanna of Anambra state southeast Nigeria. Soil samples were collected from two depths (0 -15 cm and 15 – 30 cm), at two land utilization types, and two locations, using random sampling techniques. Particle size distribution, bulk density, organic carbon, total nitrogen, pH, and soil structural stability index were analysed. The results indicated significant variations in soil properties and carbon-nitrogen stocks between land utilization types and depths. Rice fields demonstrated higher organic carbon (up to 4.72 C. Mgha-1) and nitrogen stocks (up to 0.41 N. Mgha-1) compared to cassava fields (up to 3.27 C. Mgh-1) and (up to 0.26 N. Mgha-1). The study highlighted the influence of soil texture, bulk density, and pH on carbon and nitrogen distribution. These findings emphasize the importance of adopting sustainable agricultural practices to enhance soil health, improve crop yields, and mitigate greenhouse gas emissions. The research provides a crucial baseline for further studies and informs soil management strategies in the derived savanna ecosystem.